Análisis de riesgo de desastre extensivo desde una mirada holística y bajo una escala micro: movimiento en masa en el asentamiento humano Quebrada Alta del Paraíso, distrito de Villa María del Triunfo - Sánez Zevallos, Elsa Consuelo (2021)
Urban growth in the city of Lima without a territorial multiscale focus has not been able to respond to socio-economic inequalities, ecosystem protection and disaster risks. This has meant that many populations continue to live in risk areas, as is the case of human settlements in the district of Villa María del Triunfo (VMT), exposed to «small» daily risks and cumulative impacts. In this context, this research analyzes the level of extensive disaster risk due to mass movement from a micro scale and under a holistic approach in the «Asentamiento Humano Quebrada Alta del Paraíso» through interviews, information sheets and the use of GIS.The main results of the study show a very high – high-risk level. This result is explained by the hazard analysis (very high – high), registering a total of ten active and four inactive hazards due to rock falls and landslides. Likewise, these results are conditioned by the physical characteristics of the territory that differ during the winter (Lomas ecosystem) and summer seasons. Finally, the vulnerability analysis shows a level between very high and medium level of vulnerability, which reveals the precariousness of housing and basic services (technical vulnerability); poor organization (social vulnerability); low level of education and income (economic vulnerability); the impact of the population’s knowledge and perceptions (cultural vulnerability); and the lack of institutional presence and representation (institutional vulnerability).